EDUTOURISM FOR CHILDREN OF JERUKLEUEUT VILLAGE WITH NATURAL SPACE CHILDREN GARDEN PROGRAM - Lisna Novita; Amalia Azzahra (Jurnal Abdisci, 2024)
Edutourism is an innovative approach combining education and tourism, which can bring about positive changes in children's education in rural areas. This article examines the "Natural Space Children Garden" educational tourism program in Jerukleueut Village and its impact on developing the village's children. This research involves surveys, interviews, observations, and qualitative and quantitative data analysis. The results of the study show that this program has a significant positive effect on children's understanding of the natural environment, sustainable agriculture, and social skills. They also experienced an increased interest in learning and felt a closer connection with nature. The program also provides benefits to the village community in the form of jobs and increased environmental awareness. The Natural Space Children Garden in Jerukleueut Village is a successful example of how edu-tourism can change the way children in rural areas get an education. By combining education and nature experience, the program provides invaluable benefits to children, village communities, and the environment.